Imagined states : law and literature in Nigeria, 1900-1966 - Baxter, Katherine Isobel, 1976- (Oxford : Oxford University Press, 2020)
'Imagined States' examines representations of the law in British and Nigerian high-brow, middle-brow and popular fiction and journalism. It reads works by Chinua Achebe, Joyce Cary, Cyprian Ekwensi and Edgar Wallace, together with a range of Nigerian market literature and journalism.
Previously issued in print: Edinburgh: Edinburgh University Press, 2019.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Nigerian literature -- History and criticism; Law in literature; Literature; Literature: history & criticism